Handwriting legibility across different writing tasks in school-aged children - Yael Fogel; Sara Rosenblum; Anna L. Barnett (SAGE Publishing, 2022)
Background: In school, children are required to perform a range of handwriting tasks. The writing needs to be legible to the child and other readers. The aim of this study was to examine handwriting legibility across different writing tasks and to explore which components might predict overall handwriting legibility. Methods: This was a secondary analysis of data from 148 school-aged children across writing scripts obtained from the Detailed Assessment of Speed of Handwriting: copying-best, copying-quickly and free-writing. Results: Results showed that letter formation was the major predictor of the total HLS score, and significant differences in handwriting legibility were found across the three tasks. Conclusions: The HLS is a practical tool that can benefit occupational therapists who work in schools by assessing handwriting legibility across different handwriting tasks.